Strategic Framework for Regulated Virtual Work in Healthcare & Life Sciences: A Regulated HR Policy Proposal Addressing Data Privacy, Shadow Resources, and Employee Health - J S, Ramanath (Digital Repository of Theses - SSBM Geneva, 2024)
The world of work has undergone a significant transformation with the advent of virtual work environments, particularly in the Healthcare and Life Sciences sector. This dissertation delves into the far-reaching impact of virtual work on various aspects such as employer branding, employee performance, organizational culture, data privacy, and employee health. The study employs Spearman Rank Correlation analyses to investigate the link between virtual work practices and crucial organizational outcomes. The research reveals a robust positive correlation between virtual work and employer branding, highlighting the critical role of remote work environments in attracting and retaining talent. Moreover, the study shows that employee advocacy is significantly more vigorous in virtual settings where employees feel engaged and supported, thus strengthening the employer brand. Additionally, virtual work integration is essential for effective cultural transmission and performance maintenance. New employees' ability to assimilate into company culture and uphold work ethics is significantly related to virtual work. Regarding data privacy and shadow IT, the findings indicate that virtual work does not significantly exacerbate these concerns but remains essential areas that require ongoing strategic management. While physical health impacts were minimal, mental health emerged as a moderate concern, underscoring the need for organizations to implement comprehensive support systems for employee well-being in remote work models.